What Makes Consumers Buy? The Impact of Quality, Price, Brand Image, and Social Media Promotion - Putri, Gita Amalia; Simon, Zainal Zawir (SAN Scientific, 2025)
This study was conducted to investigate the impact of Product Quality, Price Perception, Brand Image, and social media promotion on purchasing decisions for Skintific Skincare. The samples used in this study were users and users of Skintific. The sampling technique used a non-probability sampling method, with a purposive sampling technique. The data collection method used a questionnaire. Data analysis used multiple linear regression analysis. The study's results showed that product quality has a partial and significant positive effect on purchasing decisions. (2) Price perception does not have a significant effect on purchasing decisions. (3) Brand image does not have a significant effect on purchasing decisions. (4) Promotion has a positive and significant effect on purchasing decisions. The managerial implications of this study are that Skintific can improve purchasing decisions by strengthening product quality and promotion strategies on social media, as these two factors have been shown to have a significant effect. In addition, although price perception and brand image do not have a significant effect in this study, the company still needs to consider competitive pricing strategies and strengthen brand image to increase competitiveness in the market.